1995
DOI: 10.1016/0735-1097(95)00215-p
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary reperfusion therapy for cardiogenic shock: The GUSTO-I trial experience

Abstract: Because cardiogenic shock occurred most often after admission and with recurrent ischemia and reinfarction, recognizing signs of incipient shock may improve outcome. Fewer patients treated with rt-PA developed shock, yet those developing shock had the same high mortality rate as those presenting with shock, regardless of treatment. Only angioplasty was associated with a significantly lower mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(110 citation statements)
references
References 32 publications
5
101
0
4
Order By: Relevance
“…Previous trials [8,15] suggested the dominating role of STEMI in the development of CS, and our findings are consistent with those studies. CS patients who present with STEMI comprised 89.7% of all CS patients, whereas 10.3% of patients who presented with NSTEMI developed CS.…”
Section: A-v -Atrio-vetricular; Cpk -Creatinine Kinase ; Ef -Ejectionsupporting
confidence: 83%
“…Previous trials [8,15] suggested the dominating role of STEMI in the development of CS, and our findings are consistent with those studies. CS patients who present with STEMI comprised 89.7% of all CS patients, whereas 10.3% of patients who presented with NSTEMI developed CS.…”
Section: A-v -Atrio-vetricular; Cpk -Creatinine Kinase ; Ef -Ejectionsupporting
confidence: 83%
“…1,2 Cardiogenic shock remains the leading cause of death in patients hospitalized with myocardial infarction in the reperfusion era. 3,4 Nonrandomized studies report markedly lower mortality rates among patients who have undergone revascularization for shock. [5][6][7][8][9][10][11][12][13][14][15][16] However, selection bias is evident.…”
Section: Discussionmentioning
confidence: 99%
“…In GUSTO-1, patients treated with accelerated recombinant tissue plasminogen activator were significantly less likely to have shock; this finding suggests the possible benefit of early reperfusion that is associated with the use of this thrombolytic regimen. 22 We have previously documented progressive declines since the mid-1970s in the in-hospital death rates of patients with acute myocardial infarction. [17][18][19]23 We have also found declines in the rates of out-ofhospital death attributed to coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the worldwide Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries (GUSTO-1) randomized trial, cardiogenic shock developed in 7.2 percent of approximately 41,000 patients with acute myocardial infarction. 22 *The odds ratio was adjusted initially for age, sex, and medical history. The second adjustment was for age, sex, medical history, and the order (initial vs. recurrent), type, and location of the acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%